Investigating the Effects of Job Stress on the Distraction and Risky Driving Behaviors of Food Delivery Motorcycle Riders - Chen, Ching-Fu (Safety and health at work, 2023)
Occupational safety issues related to food delivery riders emerge with evidence of an increase in associated traffic accidents and injuries along with the rapid growth of the online food delivery business. This paper focuses on food delivery riders' job stress and investigates its relationships with both antecedents and risky riding outcomes. Survey data were collected from 279 Taiwanese food delivery motorcycle riders and analyzed using hierarchical regression analysis. The results show that job overload and time pressure positively impact riders' job stress, while self-efficacy slightly reduces job stress. Job stress positively leads to risky driving behavior and distraction. In addition, time pressure can strengthen the impact of job overload on job stress. Riders' risky riding attitude can also strengthen the impacts of job stress on risky riding behaviors and distraction. This paper advances the literature on online food delivery as well as the occupational safety improvement of food delivery riders. Specifically, this study provides insights into the job stress of food delivery motorcycle riders and the effects of job characteristics and risky behavioral consequences.